2014
DOI: 10.1007/s00455-014-9525-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Videofluoroscopic Swallowing Study (VFSS) Findings According to the Vascular Territory Involved in Stroke

Abstract: Dysphagia affects up to half of stroke patients and increases the risk of pneumonia and fatal outcomes. In order to assess swallowing difficulty, videofluoroscopic swallowing study (VFSS) has traditionally been the gold standard. The purpose of this study was to compare the patterns of post-stroke swallowing difficulties according to the vascular territories involved in the stroke. One hundred and three patients who were diagnosed with first ischemic stroke by brain magnetic resonance imaging and had swallowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Interestingly, Yamamoto et al (2014) have suggested that a left hemispheric stroke is associated with higher aspiration rates than a right hemispheric stroke, while territorial infarcts in posterior brain areas may result in more frequent penetration and aspiration with swallowing (Kim et al, 2014). Within the cortex, lesions of the insula (Daniels and Foundas, 1997, Daniels et al, 2006, Riecker et al, 2009), the frontal operculum (Meadows, 1973, Pender and Ferguson, 2007), and the primary sensorimotor cortex (Daniels et al, 1996) are most commonly associated with impairment of swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Yamamoto et al (2014) have suggested that a left hemispheric stroke is associated with higher aspiration rates than a right hemispheric stroke, while territorial infarcts in posterior brain areas may result in more frequent penetration and aspiration with swallowing (Kim et al, 2014). Within the cortex, lesions of the insula (Daniels and Foundas, 1997, Daniels et al, 2006, Riecker et al, 2009), the frontal operculum (Meadows, 1973, Pender and Ferguson, 2007), and the primary sensorimotor cortex (Daniels et al, 1996) are most commonly associated with impairment of swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of a similar research on time variations done recently with a population of individuals who had suffered strokes were similar. Just like in this survey, the results have shown that there was variation in OTT in the different vascular areas involved in the lesion, without, however, any significant difference regarding cortical laterality (6) . On the other hand, in the study the individuals with leftside cortical lesion have shown TOTT above 2000 ms more often than individuals with right-side lesion.…”
Section: Discussionmentioning
confidence: 62%
“…For some authors, the representation of swallowing in the cortical region in healthy individuals, using brain mapping techniques, shows that the execution of the oral phase activates more the cortical region to the left, while the following stage, the pharyngeal phase, activates the cortical region to the right (4) . This research hypothesis has been strengthened by the current studies with magnetoencephalography and magnetic functional resonance (5,6) . Thus, while the relationship between swallowing and the brain cortex is investigated and the oral stage of swallowing appears represented by the left hemisphere (7,8) , studies of the oral stage of swallowing using temporal analysis methods advance slowly.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We agree that dysphagia can be affected by white matter involvement. 3 However, unfortunately, we did not assess the accurate estimation of the degree of dysphagia by using videofluoroscopic and video endoscopic examinations. Moreover, as well known, dysphagia is basically characterized by ischemic stroke lesions and their portions.…”
mentioning
confidence: 99%